2015
DOI: 10.1097/nan.0000000000000112
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Long-Term Home Parenteral Nutrition on the Patient and the Family

Abstract: Home parenteral nutrition (HPN) is a technologically complex, life-sustaining therapy for individuals who have intestinal failure. Accepting an invasive lifelong therapy like HPN is challenging for patients and their family caregivers. There is a desire to maintain a sense of normalcy in life and to carry on as usual. Using qualitative methodology, the authors explored and described the lived experience of HPN-dependent adults and identified normalization as a repeating and strong theme. Understanding how indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 38 publications
2
35
0
Order By: Relevance
“…Such visual monitoring can prevent the frequent emergency room visits or hospitalizations that may result when early signs of problems are missed with non-visual telephone calls. Mobile connections have the added advantage of not exposing patients to infection risks from hospitals or clinic visits; as this group of patients is especially vulnerable to bloodstream infections [37]. …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Such visual monitoring can prevent the frequent emergency room visits or hospitalizations that may result when early signs of problems are missed with non-visual telephone calls. Mobile connections have the added advantage of not exposing patients to infection risks from hospitals or clinic visits; as this group of patients is especially vulnerable to bloodstream infections [37]. …”
Section: Methodsmentioning
confidence: 99%
“…Social isolation is common in this population due to patients frequently being homebound and having limited time to socialize given their daily IV treatments [39]. Our iPad mobile sessions with multiple families decreased social isolation by allowing families to share their stories and support one another around home IV care issues [40].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research revealed that HPN patients perceive their routine medical appointments as a parenteral nutrition (PN) “tune‐up” with sessions focusing primarily on medical or disease aspects of care, although they would prefer a more holistic approach with emotional support in addition to medical examination and nutrition assessment 16 . One such tool to help in this regard is a patient‐reported outcome (PRO) questionnaire.…”
Section: Introductionmentioning
confidence: 99%
“…Because there is no known PRO instrument being used in clinical practice, we developed the HPN–Patient‐Reported Outcome Questionnaire (PROQ) for patients to self‐assess factors that influence QOL or adaptation to HPN. The HPN‐PROQ was developed after a series of research activities, including comprehensive literature review, expert clinician feedback, and an exploration of the lived experiences of HPN‐dependent adults 1 , 16 , 20 , 21 . This work established a definition for QOL (“doing what I want to do when I want to do it”) and identified factors influencing QOL: eating and mealtime participation, gastrointestinal (GI) symptoms, energy level, ability to do activities of daily living, sleep, psychosocial function and coping, technology burden, and training for HPN 16 , 20 .…”
Section: Introductionmentioning
confidence: 99%